(untitled) (International Seminar on Syariah and Law (INSLA), 2021)
The Johor State Islamic Religious Council (MAIJ) was established on 1925 under the authority of Part IV, Chapter XV, Board of Regulations for the Rule of the King. There are initial functions and main functions for MAIJ. MAIJ’s initial function was to manage religious affairs, provide advice on the King’s customs, provide lessons / education to the King’s relatives and manage the welfare of the Muslim community. Meanwhile, its main function is to manage and administer the Group of Zakat & Fitrah Fund (Kumpulan Wang Zakat & Fitrah) and distribute the fund according to asnaf, manage and administer the Fund / Baitulmal Property and the Wakaf Fund as a Wakaf Trustee. This article aims to analyze the types of assistance and contributions due to Covid-19 pandemic during the Movement Control Order (MCO) on 18 March 2020 to 31 March 2020 organized by the Johor Islamic Religious Council. This study is a qualitative study with content analysis design. The results show that the Johor Islamic Religious Council provides assistance to people in need with a set amount along with the number of recipients to be in line with the budget. This study lists the types of donations along with the amount of aid money as a reference for recipients during the period of the Movement Control Order (MCO) Abstrak Majlis Agama Islam Negeri Johor (MAIJ) telah ditubuhkan pada tahun 1925 di bawah kuatkuasa Bahagian IV, Bab XV, Lembaga Aturan Bagi Pemerintahan Raja. Terdapat fungsi awal dan fungsi utama bagi MAIJ. Fungsi awal MAIJ ialah menguruskan hal ehwal agama, memberi khidmat nasihat mengenai adat istiadat Raja, memberi pelajaran / pendidikan kepada kerabat Di Raja dan menguruskan kebajikan masyarakat Islam. Manakala, fungsi utamanya ialah menguruskan dan mentadbir Kumpulan Wang Zakat & Fitrah dan mengagihkan mengikut asnaf, mengurus dan mentadbir Kumpulan Wang / Harta Baitulmal dan Kumpulan Wang Wakaf sebagai Pemegang Amanah Wakaf. Artikel ini bertujuan untuk menganalisis jenis-jenis bantuan dan sumbangan Covid-19 sepanjang Perintah Kawalan Pergerakan (PKP) 18 Mac 2020 hingga 31 Mac 2020 yang dianjurkan oleh Majlis Agama Islam Negeri Johor. Kajian ini adalah kajian kualitif dengan reka bentuk analisis kandungan. Hasil kajian menunjukkan bahawa Majlis Agama Islam Negeri Johor memberi bantuan kepada orang yang memerlukan dengan jumlah yang ditetapkan beserta jumlah penerima supaya selaras dengan belanjawan. Kajian ini menyenaraikan jenis sumbangan beserta jumlah wang bantuan sebagai rujukan untuk penerima sepanjang tempoh Perintah Kawalan Pergerakan (PKP)